Primary Liver Tumor? Not Everything Is What It Seems. - Luís Miguel Relvas; Sónia Barros; Isabel Carvalho; Francisco Velasco (Galicia Clínica)
Germ cell tumors of gonadal or extragonadal origin are curable solid tumors, due to their good sensitivity to chemotherapy. The vast majority of cases present as a result of testicular symptoms and in a minority, as metastatic dissemination. We present a case of a “burned-out” tumor, in which the presentation was mainly caused by metastases, and clinical confounders led to the suspicion of hepatocellular carcinoma, delaying the correct diagnosis. We emphasize the importance of considering germ cell tumors, especially in young men with liver and lung metastases as a differential diagnosis. Knowing that it is a tumor that tends to grow rapidly, but is curable in most cases, delay in diagnosis can make it difficult to treat a patient in inadequate conditions.